A Platform for Validating Colorectal Cancer Driver Genes Using Mouse Organoids - Takeda, Haruna (Frontiers in Genetics, 2021)
Systematic approaches for functionally validating cancer genes are needed since numerous genes mutated in cancer tissues have been identified from cancer genome sequencing. The mouse organoid culture system has been extensively used in the field of cancer research since mouse organoids can faithfully recapitulate the physiological behavior of the cells. Taking advantages of this, we recently described a platform for functionally validating colorectal cancer (CRC) driver genes that utilized CRISPR-Cas9 in mouse intestinal tumor organoids. In this review, we will describe how mouse organoids have been applied to the CRC research and focus on how CRC genes can be validated using mouse organoids.